Information Seeking Behaviour: A Catalyst for Library Resources Utilization by Undergraduate’s in University Of Calabar - David-West, Boma Torukwein; Bassey, Mary Mfon (Communicate: Journal of Library and Information Science, 2023)
This study examined information seeking behaviour: A catalyst for library resources utilization by undergraduates of University of Calabar. Three research questions and three hypotheses guided the study. Descriptive survey design was adopted for the study. The population of the study comprises 136 undergraduate students of the department of Library and Information Science University of Calabar. Census sampling technique was used for the study. A questionnaire was used for data collection. The instrument was tested for reliability. Yielding Cronbach,s Alpha coefficient at 0.75 making it valid and reliable. A total of 136 copies of the instrument was administered to respondents. At the end, 102 copies of the instrument were retrieved representing 75% return rate. The research question was answered using descriptive statistics of ( x) while the hypotheses was tested using z test statiscal analysis at 0.5 alpha level. The study revealed that there is a significant influence of information seeking behaviour on utilization of library resources. It was concluded that academic libraries should provide the right information at the right time in the right format to its patrons, selecting sources, refining sources and evaluating sources are key to utilizing library resources. It recommended among others Library management should provide current library resources and online databases for easy access and retrieval.